The Role of Beta-hCG Progesterone and Creatine Kinase in the Early Diagnosis of Ectopic Pregnancies - Nagihan Sarı; Hatice Işık; Hatice Başar; Ali Seven; Ahmet Bostancı (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: As ectopic pregnancy (EP) is an important cause that threatens life in the first trimester of pregnancy, the early diagnosis is important. The present study investigated the role of creatine kinase, progesterone and beta-hCG in the early diagnosis of EP. STUDY DESIGN: Seventy-three patients admitted to Ankara Education and Research Hospital out-patient clinics. The patients were divided into three groups: Group 1; patients admitted to family planning unit for induced abortion (n=22), Group 2: patients diagnosed as spontaneous or missed abortion (n=23), Group 3; patients diagnosed as ectopic pregnancy (n=28). Serum samples were taken from patients for β-hCG, progesterone and creatine kinase before any management. SPSS for Windows 11,5was used for the analysis of the data. RESULTS: Serum progesterone levels in normal pregnancies were statistically significantly higher than the levels in other two groups (p<0.001). But the progesterone levels in spontaneous abortion and ectopic pregnancy groups were not significantly different from each other. The best cut-off point for progesterone was determined as 14ng/ml with 94.1% specificity and 81.8% sensitivity. Serum β-hCG levels in normal pregnancy group were statistically significantly higher than abnormal pregnancies (missed, spontaneous abortion and ectopic pregnancy). The creatine kinase levels of the groups were not significantly different. CONCLUSION: Serum biomarkers, β-hCG and progesterone are helpful for early diagnosis of abnormal pregnancy but could not be helpful to differentiate ectopic and abnormal intrauterine pregnancies. Creatine kinase is not helpful to differentiate EP and normal pregnancies.